Active Learning Approaches to Teaching Soil Science at the College Level - Amador, Jose A. (Frontiers in Environmental Science, 2019)
Traditional passive approaches to teaching, such as lectures, are not particularly effective at promoting student learning, or at developing the qualities that employers seek in graduates from soil science programs, such as problem-solving and critical thinking skills. In contrast, active learning approaches have been shown to promote these very qualities in students. Here I discuss my use of active learning approaches to teach soil science at the introductory and advanced levels, with particular focus on problem-based learning, and combined just-in-time teaching and peer instruction. A brief description of the each pedagogical approach is followed by evidence of its impact on student learning in general and, when available, its use in soil science courses. I describe and discuss my experiences using these approaches teaching introductory soil science (face-to-face and online), soil chemistry and soil microbiology courses, and provide examples of some of the problems I use. I have found the benefits to student learning in terms of student engagement, ownership of learning, and development of critical thinking and problem-solving skills easily outweigh are clear relative to traditional, passive approaches to teaching.